'Impossible to implement?': The effectiveness of anti-homophobia policy in English professional football. Issue 1 (2nd January 2019) - Magrath, Rory; Stott, Peter
ABSTRACT: Anti-discrimination initiatives have been part of a significant change in English football over the past three decades. Influential work by organisations such as Kick It Out —particularly for issues of racism—have seen a sharp decline in overt forms of discrimination inside English football stadia. Spectator disorder in football stadia is no longer as commonplace as it was throughout the 1970s and 1980s. Despite overwhelming academic evidence indicating that homophobia in football has declined, great emphasis has also been placed by the game's governing body, the Football Association (FA), to ensure its culture is unconditionally inclusive. In this article, we adopt institutional analysis of the FA's most recent anti-homophobia policy, Opening Doors and Joining . We then draw on 53 semi-structured interviews with English football fans' perceptions on the success of this policy, highlighting that while some progress has been made, there are still numerous shortcomings of the FA's attempts to implement change on the game. The article concludes with fan recommendations to challenge issues of homophobia more effectively.